Uterus transplantation from the perspective of bioethical principles: A review study - Sakineh Taherkhani (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2021)
Introduction: Uterus transplantation, as a treatment method for absolute uterine infertility, is still in the experimental stage. It is necessary to determine the ethical feasibility of uterus transplantation before using it as a standard treatment for absolute uterine infertility. Therefore, this study was conducted with aim to review uterus transplantation from the perspective of bioethical principles. Methods: In this review study, to find the related articles, the databases of SID, MagIran, Irandoc, PubMed and Iran Medical Articles Bank were searched. The search was conducted without any limitation in Persian databases until June 20, 2020 and in English databases until March 20, 2020. After acquiring the relevant articles, the ethical issues mentioned in them regarding uterus transplantation were identified and classified in principles of bioethics. Results: From 92 identified articles, 48 papers were entered the study for qualitative review. Based on the results, from the perspective of the principle of autonomy, uterus transplantation is a step towards achieving the reproductive autonomy. From the perspective of the principle of beneficence, in addition to the possibility of giving birth to a healthy baby by the recipient, treating infertility through transplantation has many benefits for the recipient and donor. From the perspective of the principle of non-maleficence, extensive efforts have been made to identify, reduce and eliminate transplantation risks; however, a proper balance of benefit and loss is essential to perform the transplantation. From the perspective of the principle of justice, some criteria have been considered for the fair allocation of transplant uterus, but funding of the transplant is still debated. Conclusion: From the perspective of the principles of autonomy, beneficence and non-maleficence, ethically performing of uterine transplantation is possible. Currently, the most ethical discussion in the field of uterus transplantation is related to the principle of justice.